Edukasi Gizi Pencegahan Dan Penanganan Anemia Pada Atlet Muda Wanita Di Papua - Sutoro Sutoro; Tri Setyo Guntoro; Evi Sinaga; Miftah Fariz Prima Putra; Rodhi Rusdiyanto Hidayat; Eva Sinaga; Ansar CS (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Anemia is one of the crucial problems that are often experienced by female athletes. The occurrence of anemia in athletes will cause the training process cannot run optimally so that the increase in ability at a higher level does not occur. The purpose of this community service was to increase the knowledge of athletes, teachers and coaches, especially female athletes by providing nutritional education about the prevention and management of anemia in SMANKOR Papua. Thus, the creation of the good physical condition of female athletes who are able to score achievements. This activity took the form of nutritional education conducted by giving materials, discussions, evaluations and mentoring. The activity began with a pre-test and was done post-test at the end of the activity. The event was conducted online attended by students, teachers and coaches of SMANKOR Papua. The results showed differences in knowledge of students, teachers and coaches about the prevention and management of anemia, before and after nutrition education and mentoring. Thus, it can be concluded that nutrition education and assistance regarding the prevention and management of anemia affect the knowledge of students, teachers and coaches at SMANKOR Papua